On the study of vortex-induced vibration of circular cylinders covered with different roughness. (July 2022) - Sun, Chenlin; Zhou, Tongming; An, Hongwei; Zhu, Hongjun; Cheng, Liang
Abstract: The existence of roughness changes the surface conditions of a cylindrical structure and hence influences its hydrodynamic properties. The present study focused on the vortex-induced vibration (VIV) responses of circular cylinders covered with different roughness heights and coverage ratios. Three relatively large roughness heights ( k/D  = 5%, 10% and 20%) and three coverage ratios ( CR  = 20%, 46%, and 79%) were considered. Cylinders with hemispherical roughness were prepared through 3D printing and were tested in a wind tunnel to examine their VIV characteristics. It is found that the surface roughness can effectively suppress the VIV responses and narrow the lock-on region. Specifically, the VIV suppression effects are improved by increasing the roughness height and by reducing the roughness coverage ratio based on the cases covered in this study. A maximum VIV reduction of 53% compared to that of the smooth cylinder can be achieved for a rough cylinder with k/D  = 20% and CR  = 20%. To further explore the physical mechanisms for VIV reduction by different coverage ratios, wake characteristics of cylinders covered with k/D  = 10% and the above three coverage ratios were examined using particle image velocimetry (PIV) in a water flume. The results show that with the increase in CR, the vortex formation length increases, and the Strouhal number reduces gradually. In addition, with the increase in CR, the magnitudes of the turbulent kinetic energy and the Reynolds stresses also increase. This is because the increase in CR motivates the formation of the large-scale coherent structures in the wake.